Background predictors of self-effi cacy beliefs of Iranian EFL teachers working in English Language Centers - Ghasemboland, Farimah (Penerbit UKM, 2015)
It has been shown that teachers’ self-effi cacy infl uences teachers’ actions and student outcomes. The present study explored self-effi cacy beliefs of English as Foreign Language teachers in the language centres in one selected middle-east country, Iran. The needed data was collected by administering a survey to 187 teachers. The Teacher Sense of Effi cacy Scale was used to assess effi cacy for engagement, management, and instructional strategies. Results show that teachers’ perceived effi cacy correlate with some of teachers’ background characteristics. Results also indicate that teachers’ classroom management effi cacy was higher than instructional strategies and student engagement effi cacy. Employing the multiple regression analysis, it was shown that different sets of background variables were signifi cant in predicting the self-effi cacy dimensions of the teachers of this study.